Multi-beam accelerating module calculation - Gavrilov, N.M.; Alexeyenko, S.V.; Komarov, D.A.; Netchaev, N.N.; Struckov, J.N. (Вопросы атомной науки и техники, 1999)
As has been pointed in [1], a multi-beam accelerating cavity with drift tubes is suggested to be used in a linac for the purpose of overcoming limitations on the mean current. In this paper the dispersion equation for such a construction was deduced and analyzed.